The relation between aggression and theory of mind in children: A meta‐analysis. Issue 2 (6th September 2022) - Wang, Yiyi; Shang, Siyuan; Xie, Wanze; Hong, Skylar; Liu, Zexi; Su, Yanjie
Abstract: Previous findings on the association between theory of mind (ToM) and aggression in children are mixed. The social skills deficit view regarded ToM as a single‐edged sword and proposed that a lack of ToM can lead to aggression, while the double‐edged sword view proposed that children with advanced ToM can still show much aggression because children can also leverage ToM to harm others. To resolve the dispute between the two views, we conducted a meta‐analysis combining cross‐sectional and longitudinal findings from 53 studies including a total of 11, 579 children aged between 2 and 15 years. The overall negative correlation between ToM and aggression was small but significant ( r = −0.08). The negative correlation was robust, with the magnitude of the correlation being similar across physical versus relational aggression, proactive versus reactive aggression, cognitive versus affective ToM, preschoolers versus school‐aged children, different aggression measurements, and different levels of societal individualism. Moreover, the negative correlation was found regardless of whether ToM and aggression were measured concurrently or at different time points, but the correlation was the largest when ToM was measured before aggression. Whether the aggression was bullying or not also moderated the association, with ToM only being negatively related to non‐bullying aggression but not bullying. Together, these findings suggest that ToM is a single‐edged sword to decrease general aggression and that aggression might also give rise to lower ToM capacity during development. Research Highlights: This study systemically reviewed the existing mixed findings on the association between aggression and ToM during childhood using a meta‐analysis. There was a negative correlation between ToM and aggression in children aged between 2 and 15 years. The negative correlation between aggression and ToM was stronger when ToM was measured first, followed by aggression, than vice versa. There was a negative correlation between non‐bullying aggression and ToM, whereas there was no correlation between bullying and ToM. Abstract : Using a meta‐analysis, this study found a negative correlation between ToM and aggression in children aged between 2 and 15 years. The negative correlation between aggression and ToM was stronger when ToM was measured first, followed by aggression, than vice versa. There was a negative correlation between non‐bullying aggression and ToM, whereas there was no correlation between bullying and ToM.